Pengaruh Pertumbuhan Aset, Profitabilitas, dan Pertumbuhan Penjualan Terhadap Struktur Modal Pada Perusahaan Real Estate Dan Properti Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2012 - Ranti Agus Astuti; Kirmizi Ritonga; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The capital structure is important for any company, because the company can not be separated from the debt. Many factors can affect the debt in a company becomes important as a basis in determining the composition of the capital structure of the company. Factors to be examined alleged effect on the capital structure including asset growth, profitability, and sales growth. The purpose of this study was to determine the effect of asset growth, profitability, and sales growth on the company's capital structure. Based on the results of research and discussion on this study, it can be concluded that the Asset Growth, Profitability, and Sales Growth had no significant effect on the capital structure and property Real Estate company that went public at the Indonesia Stock Exchange (IDX) 2010-2012.Keywords : Asset Growth, Profitability, Sales Growth, and Capital Structure